2017
DOI: 10.1175/waf-d-16-0182.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Assimilating Underwater Glider Data on Hurricane Gonzalo (2014) Forecasts

Abstract: The initialization of ocean conditions is essential to coupled tropical cyclone (TC) forecasts. This study investigates the impact of ocean observation assimilation, particularly underwater glider data, on high-resolution coupled TC forecasts. Using the coupled Hurricane Weather Research and Forecasting (HWRF) Model–Hybrid Coordinate Ocean Model (HYCOM) system, numerical experiments are performed by assimilating underwater glider observations alone and with other standard ocean observations for the forecast of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 52 publications
6
40
1
Order By: Relevance
“…Assimilation of ALPS measurements reduces the upper-ocean thermal bias and corrects errors in the representation of mesoscale features in the initial oceanic fields. Dong et al (2017) demonstrate the positive impact of assimilating oceanic observations on ocean model initialization and TC intensity forecasts. ALPS are also important for evaluating ocean model performance, devising strategies to improve their performance, ABSTRACT.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Assimilation of ALPS measurements reduces the upper-ocean thermal bias and corrects errors in the representation of mesoscale features in the initial oceanic fields. Dong et al (2017) demonstrate the positive impact of assimilating oceanic observations on ocean model initialization and TC intensity forecasts. ALPS are also important for evaluating ocean model performance, devising strategies to improve their performance, ABSTRACT.…”
Section: Introductionmentioning
confidence: 80%
“…The presence of this barrier layer may have favored the storm's intensification, as Gonzalo continued intensifying into a Category-4 hurricane . Observations collected by the glider before (July 15 to October 13, 2015), during, and after the passage of Gonzalo were assimilated into the high-resolution Hurricane Weather Research and Forecasting (HWRF)-Hybrid Coordinate Ocean Model (HYCOM) coupled forecast system (Dong et al, 2017). Results indicated that assimilation of the underwater glider observations significantly improved the pre-storm thermal and saline model initializations, in particular, the barrier layer (Figure 6b).…”
Section: Alps-enabled Improvements In Tc Ocean-induced Dynamics and Imentioning
confidence: 98%
See 1 more Smart Citation
“…Clearly, ocean observations are vital in ECs and TCs research and forecasts, since they enable examining the details of air-sea interaction processes that can lead to the formation and intensification of these systems (e.g., Leipper and Volgenau, 1972;Sanders and Gyakum, 1980;Mainelli et al, 2008;Kuwano-Yoshida and Minobe, 2017). In addition, ocean observations have been increasingly acknowledged by the forecast community as a critical piece to improve extreme weather forecasts (e.g., Dong et al, 2017). Their important role will likely continue to increase in light of improvements in coupled model capabilities (see below), and future extreme weather projections, which expects intense weather systems to become more frequent (e.g., Colle et al, 2015;Bacmeister et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The upper ocean is influenced by TCs (e.g., Price, 1981Price, , 1983Price et al, 1994), and the feedback affects the TC development (e.g., Bruneau et al, 2018;D'Asaro et al, 2007;Halliwell et al, 2015;Schade & Emanuel, 1999). Thus, oceanic observations have been assimilated in the TC forecast systems, including both in situ (e.g., Dong et al, 2017;Goni et al, 2017) and satellite (e.g., Halliwell, Mehari, Shay et al, 2017) observations. However, the spatial coverage of in situ observations is quite limited, especially in the coastal regions, and the satellite observations can be infrequent, impacted by clouds, and are of coarse resolution.…”
Section: Introductionmentioning
confidence: 99%